Acute Appendicitis in Pregnancy: An Update Towards Effective Diagnostic and Treatment Approaches - Kumar Hari Rajah (Medicine and Medical Research: New Perspectives Vol. 1, 2024)
Acute appendicitis in pregnancy is a challenging non-obstetric abdominal condition that is encountered by the general surgeon. The clinical presentation and diagnosis of this condition are difficult due to the presence of the gravid uterus. The physiological changes that occur in pregnancy make interpretation of investigations like full blood count difficult. Imaging modalities are also hampered by the risk of radiation exposure to the fetus, so ultrasonography and magnetic resonance imaging are most used. The treatment of acute appendicitis in pregnancy is appendectomy which can be performed by an open and laparoscopic method. In this chapter we will look at the diagnosis and treatment of acute appendicitis in pregnancy, looking at the role of laparoscopic appendectomy in pregnancy.